Advances in enzymatic conversion of biomass derived furfural and 5-hydroxymethylfurfural to value-added chemicals and solvents. (June 2023) - Kumar Vaidyanathan, Vinoth; Saikia, Kongkona; Senthil Kumar, P.; Karanam Rathankumar, Abiram; Rangasamy, Gayathri; Dattatraya Saratale, Ganesh
Graphical abstract: Highlights: Furans-based biorefineries for the transformation of HMF and furfural was discussed. A perspective on the use of furan-based value-added chemicals was discussed. Role of lipase and oxidases in the synthesis of HMF esters and FDCA is highlighted. Compare to HMF, enzymatic conversion of furfural remain far less investigated. Challenges and scope of future research in enzymatic furans conversion is reviewed. Abstract: The progress of versatile chemicals and bio-based fuels using renewable biomass has gained ample importance. Furfural and 5-hydroxymethylfurfural are biomass-derived compounds that serve as the cornerstone for high-value chemicals and have a myriad of industrial applications. Despite the significant research into several chemical processes for furanic platform chemicals conversion, the harsh reaction conditions and toxic by-products render their biological conversion an ideal alternative strategy. Although biological conversion confers an array of advantages, these processes have been reviewed less. This review explicates and evaluates notable improvements in the bioconversion of 5-hydroxymethylfurfural and furfural to comprehend the current developments in the biocatalytic transformation of furan. Enzymatic conversion of HMF and furfural to furanic derivative have been explored, while the latter has substantially overlooked a foretime. This discrepancy was reviewed along with the outlook on the potential usage of 5-hydroxymethylfurfural and furfural for the furan-based value-added products' synthesis.